Respiratory Rehabilitation for A Loss to Follow-Up Pulmonary Tuberculosis Patient with Bilateral Hydropneumothorax: A Case Report - Isdyanta, Rezky Achmad; Widjanantie, Siti Chandra (Respiratory Science, 2025)
Background: Tuberculosis (TB) is a preventable and treatable disease. However, without treatment, mortality from TB is 50%, whereas with treatment, 85% of people with TB can be cured. Incomplete treatment of pulmonary TB can lead to various complications, one is hydropneumothorax, which is an abnormal picture of air and fluid in the pleural cavity. Complications of this condition can lead to long-term impairment of lung function with varying degrees of severity. Pain and shortness of breath are clinical features that interfere with daily activities and are associated with a decreased quality of life. Pulmonary rehabilitation is a crucial component in managing respiratory diseases, including pneumothorax, which aims to restore respiratory muscle strength, optimize lung expansion, and prevent complications such as atelectasis, pleural adhesions, or chronic respiratory insufficiency. Case: A 26-year-old woman presented to the emergency department with moderate dyspnea. She was diagnosed with loss to follow-up (LTFU) TB with bilateral hydropneumothorax and malnutrition. She was in the third month of a four-drug anti-TB regimen and had a chest tube with water shield drainage (WSD) placed in both the right and left chest walls. The rehabilitation problems in these patients are dyspnea, pain in the chest tube insertion area, immobilization, and partial dependency. Discussion: A pulmonary rehabilitation program was initiated during hospitalization and continued in the outpatient rehabilitation clinic, including energy conservation techniques, breathing exercises, relaxation, splinted cough, chest wall mobilization, respiratory muscle stretching, and laser therapy for pain management. Barthel Index (BI) shows improvement from 10 to 45 due to pain reduction. Visual Analog Scale (VAS) 7-8 to 5, allowing the patient to use her right upper extremity for daily activities. Conclusion: Pulmonary rehabilitation is a cost-effective therapy that can improve symptoms and quality of life in patients with post-TB hydropneumothorax. It also reduces spasms, dyspnea, and pain.